Pengaruh Pengetahuan dan Pemahaman Masyarkat Muslim Kepada Bank Syariah Terhadap Minat Setelah Merger Bank Syariah Indonesia - Sabirin, Sabirin (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2024)
The purpose of this study is to find out: (1) The influence of knowledge of the Muslim community on Sharia Banks on interest after the merger of Bank Syariah Indonesia. (2) The influence of the understanding of the Muslim community on Sharia Banks on interest after the merger of Bank Syariah Indonesia. (3) The influence of knowledge and understanding of the Muslim community on Sharia Banks simultaneously on interest after the merger of Bank Syariah Indonesia. This type of research is quantitative. The population is the Muslim community of East Pontianak District. Sampling used probability sampling techniques with simple random sampling using the Slovin formula. The data collection method used a questionnaire using Google Form which was distributed to 100 samples of the East Pontianak Muslim community. Data were processed using SPSS 21. Data analysis used multiple linear regression. The results of this research show that: (1) The Muslim community's knowledge of Sharia Banks has a positive effect on interest in using Sharia Banks after the merger of Bank Syariah Indonesia. (2) The Muslim community's understanding of Sharia Banks has a positive effect on interest in using Sharia Banks after the merger of Bank Syariah Indonesia. (3) The Muslim community's knowledge and understanding of Sharia Banks simultaneously has a positive influence on interest in using Sharia Banks after the merger of Bank Syariah Indonesia